THE ANALYZE OF CUSTOMERS WILLINGNESS TO BUY INDOMARET’S PRIVATE LABEL PRODUCTS AT INDOMARET KAUDITAN - Tirayoh, Felicia; Massie, James D. D.; Arie, Fitty Valdy (Universitas Sam Ratulangi, 2019)
Abstract: Increasing consumption of goods and services creates the rapid growth of retail business in Indonesia from year to year. Modern retail business is experiencing rapid growth in the last few years. Therefore, The objective of this research is to analyze customer willingness to buy Indomaret’s private label products. This research used quantitative analysis. The population in this research refers to the consumers of Indomaret Kauditan and samples used in this study of 100 respondents. The results showed Store image, perceived price, perceive quality and perceived value have a significant effect on willingness to buy Indomaret’s private label products simultaneously. Store image has significant effect on willingness to buy Indomaret’s private label products partially. Perceived price does not have a significant effect on willingness to buy Indomaret’s private label products partially. Perceived quality does not have a significant effect on willingness to buy Indomaret’s private label products partially. Perceived value has significant effect on willingness to buy Indomaret’s private label products partially. Indomaret Kauditan should pay attention to the price and quality of the products, thereby can increase customers willingness to buy Indomaret’s private label products. Keywords: willingness to buy, store image, perceived price, perceived quality, perceived value